2018
DOI: 10.3390/soilsystems2020034
|View full text |Cite
|
Sign up to set email alerts
|

Release and Biomethylation of Antimony in Shooting Range Soils upon Flooding

Abstract: Antimony (Sb) is an understudied pollutant with potentially toxic effects at particularly low concentrations. The fate of Sb in the environment is complicated because of its many chemical forms at varying oxidation states. Here, we validated an extraction method and an analytical technique to quantify inorganic and methylated Sb in bulk soil and soil solution. We identified and quantified trimethylantimony (TMSb) in shooting range soils for the first time, up to a concentration of 1.35 mg kg −1 . Then, we eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 64 publications
3
16
1
Order By: Relevance
“…Sb has been reported to exceed the value of 5000 mg/kg when background concentration in the natural environment is only 0.2 mg/kg, and the maximum permissible concentration according to the World Health Organization (WHO) is set at 36 mg/kg [ 3 , 10 , 11 ]. The predominant species are Sb(V) under oxic conditions and Sb(III) under reducing conditions [ 12 ]. In active Sb mining areas, a high Sb fraction is bioavailable, comprised primarily of Sb(V) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sb has been reported to exceed the value of 5000 mg/kg when background concentration in the natural environment is only 0.2 mg/kg, and the maximum permissible concentration according to the World Health Organization (WHO) is set at 36 mg/kg [ 3 , 10 , 11 ]. The predominant species are Sb(V) under oxic conditions and Sb(III) under reducing conditions [ 12 ]. In active Sb mining areas, a high Sb fraction is bioavailable, comprised primarily of Sb(V) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Restricted oxygen diffusion in soils and sediments induced by waterlogging and fluctuating water tables influence metal(loid) mobility by shifting microbial communities to alternative electron acceptors for energy, such as Mn IV and Fe III -(oxyhydr)oxides coupled to the oxidation of organic C [16,22,23,[26][27][28]. Sb typically forms inner-sphere complexes with Fe III -and Mn IV -(oxyhydr)oxides in soils and sediments, and periodic or permanent waterlogging can induce Sb release by reductive dissolution of the host phases [26,27,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Restricted oxygen diffusion in soils and sediments induced by waterlogging and fluctuating water tables influence metal(loid) mobility by shifting microbial communities to alternative electron acceptors for energy, such as Mn IV and Fe III -(oxyhydr)oxides coupled to the oxidation of organic C [16,22,23,[26][27][28]. Sb typically forms inner-sphere complexes with Fe III -and Mn IV -(oxyhydr)oxides in soils and sediments, and periodic or permanent waterlogging can induce Sb release by reductive dissolution of the host phases [26,27,29,30]. Soluble Sb can be subsequently sequestered with waterlogging due to stronger adsorption of Sb III to Fe-phases in the soil [23,29], immobilized by sulfides [3,31,32], or Fe II catalyzed Fe III -phase transformations at neutral conditions, which incorporate Sb V into authigenic Fe III -phases (e.g., goethite and feroxyhyte) [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frohne et al ( 2011 ) suggested that low redox potential promotes the mobility of methylated Sb, based on the observation that the concentrations of mono- and di-methylated Sb decreased linearly with increasing redox potential in a soil suspension. Grob ( 2016 ) detected TMSb in the pore water of shooting range soils after 4 days of waterlogging, and Yang and He ( 2016 ) found higher concentration of methylated Sb in paddy soils than in dryland soils. Furthermore, the volatile compound trimethylstibine was found in sewage sludge sampled from anaerobic wastewater (Michalke et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%